Modelling of plasma performance and transient density behaviour in the H-mode access for ITER gas fuelled scenarios. (5th August 2015) - Romanelli, M.; Parail, V.; da Silva Aresta Belo, P.; Corrigan, G.; Garzotti, L.; Harting, D.; Koechl, F.; Militello-Asp, E.; Ambrosino, R.; Cavinato, M.; Kukushkin, A.; Loarte, A.; et al.
Abstract: ITER operations require effective fuelling of the core plasma for conditions in which neutral dynamics through the scrape-off layer is expected to significantly affect the efficiency of gas penetration. On the basis of the previous analysis for stationary conditions, pellets are foreseen to provide core fuelling of high-Q DT scenarios. In this paper we present a modelling study of the gas fuelling efficiency in ITER providing an estimate of the maximum plasma density achievable with gas fuelling only in various DT reference scenarios. Dynamical integrated core-edge plasma simulations for various phases of ITER DT H-mode discharges have been carried out with the JINTRAC suite of codes. Simulations of the L-mode phase show that divertor detachment sets the maximum density achievable at the separatrix by deuterium-tritium gas fuelling. The maximum volume-average density is achieved for 15 MA/5.3 T and it is close to the requirement for stationary application of neutral beam injection heating at full power (16.5 MW per injector) and ion energy (1 MeV) compatible with acceptable shine-through loads on the first wall. The achievable density in gas fuelled H-modes is typically a factor of 2–3 larger than in L-modes. The fusion performance of gas fuelled H-modes at 15 MA is typically found to be moderately high ( Q ~ 6–8). Sensitivity of the above predictions to modelling assumptions and validation of the physics models are discussed.